Latest FLUKA developments - Hugo Gabrielle; Ahdida Claudia; Bozzato Davide; Calzolari Daniele; Cerutti Francesco; Ciccotelli Alessia; Cimmino Anna; Devienne Arnaud; Donadon Servelle Andre; Dyrcz Patrycja K.; Salvatore Esposito Luigi; Formento Alice; et al. (EPJ Nuclear Sciences & Technologies)
The FLUKA Monte Carlo code has recently undergone significant enhancements, driven by needs from its user community. Key improvements are discussed, such as a new point-wise treatment for the interactions of low-energy neutrons, the incorporation of a new model for nuclear elastic scattering of protons below 250 MeV, explicit generation of synchrotron radiation photons during charged particle tracking, a revised modeling approach for coherent effects in bent crystals, and the addition of arc-DPA scoring. While improving and extending FLUKA physics performance is essential, it is equally important to ensure the long-term maintainability of the codebase. This paper also outlines the strategy and substantial progress in evolving FLUKA to meet this objective. The FLUKA features are being translated into a new codebase, fulfilling essential criteria such as continuity in the user experience and compatibility with existing inputs, thus laying the foundation for a new FLUKA generation. The codebase makes use of the Geant4 toolkit when appropriate. Additionally, the enhanced collaboration with Geant4 has resulted in the development of an interface, detailed in this paper, that enables access to the FLUKA hadronic models from any Geant4 application.